Motivated perception: discovering emotional bias in mood judgements using the mood-of-the-crowd paradigm - Mertens, Alica (2019)
Previous research on valence biases in face perception revealed inconsistent findings either proposing angry or happy faces to be detected more efficiently. Most studies in this field used the face-in-the-crowd (FiC) paradigm, in which participants have to judge whether there is a divergent face in a crowd of distractor faces. However, this task leads to ambiguous results because it is not entirely clear whether effects are based on a fast perception of the target or the distractor faces surrounding it. The newly developed mood-of-the-crowd (MoC) paradigm can complement existing FiC findings. Instead of deciding whether there is a deviating face in a crowd of distractors, this novel paradigm uses multiple target emotions, eliminating the differentiation between target and distractors. In addition to investigating general biases in emotion perception with this new paradigm, the examination of the stability of perceptual biases over the life span and the moderating role of individual differences (fear of rejection) and stimuli characteristics (face attractiveness) were of main focus. In all studies, eye-tracking procedures were implemented to further illuminate the individual’s search processes when using the novel mood-of-the-crowd paradigm.